Detecting underground structures in vegetation indices time series using histograms - Melillos, George; Hadjimitsis, Diofantos G. (My University, 2020)
This paper focuses results obtained from a field spectroscopy campaigns for detecting underground structures. A number of vegetation indices such as the Normalized Difference Vegetation Index (NDVI), Simple Ratio (SR), Enhanced Vegetation Index (EVI) and Ratio Vegetation Index (RVI) were utilized for the development of a vegetation index-based procedure aiming at the detection of underground military structures by using existing vegetation indices. The measurements were taken at the following test areas such as: (a) vegetation area covered with the vegetation (barley), in the presence of an underground military structure (b) vegetation area covered with the vegetation (barley), in the absence of an underground military structure. For this purpose was using histograms to obtain useful information about Vegetation Indices spectral behaviours and to compare the two testing areas.
Keywords: EVI; Field Spectroscopy; Histograms; NDVI; Remote sensing; RVI; SR; Vegetation indices